Pengaruh Pengendalian Intern Terhadap Efektivitas Biaya Perjalanan Dinas - Irma Suryani; Muhammad Syahrudin; Frans Yohanes (Department of Accounting-Faculty of Economic and Business (FEB), 2022)
Business travel is a cost that quite affects cash disbursements, so it is necessary to carry out effective controls to prevent fraud. The company has implemented internal control but there are still some irregularities in the management of official travel expenses. This study aims to analyze the influence of internal control on the cost effectiveness of official travel at Shafira Corporation. The research method uses quantitative research methods. Sources of data obtained from primary data with data collection through filling out a questionnaire given to 31 respondents who are employees of the company and the author’s direct observations. Data analysis used a simple regression method. The results of the study indicate that the internal control system affects the effectiveness of official travel expense where the elements of internal control have been implemented so as to minimize the risk of fraud and violations of official travel expense. The results of this study will have an impact on the cost of official travel which is carried out in accordance with budget standards and work programs that have been determined through the implementation of internal control functions.